Understanding gifted adolescents in Singapore : a Dabrowskian perspective - Mike Mariyappa Thiruman. (2008)
The purpose of the study was to provide a framework for understanding the characteristics of the intellectually gifted adolescents in Singapore based on Dabrowski's (1996) overexcitabilities (OEs). As OEs highlight the heightened sensitivity and intensity of the gifted, they serve as an appropriate framework for analyzing and understanding the gifted adolescents' affective needs (Piechowski, 1997; Ackerman, 1997a). Gifted pupils (n=240) from Secondary One to Four formed the gifted sample. Of these 240 gifted pupils, data from 60 Secondary Two and Three pupils were used in a comparison analyses. The comparison group was made up of 60 Secondary Two and Three pupils from the mainstream, who were classified as "non-gifted" for the purpose of this study. All the subjects completed the 50-item Likert-scale Overexcitability Questionnaire-Two (OEQII).